DEVELOPING INTERACTIVE MULTIMEDIA-BASED INSTRUCTIONAL MEDIA WITH ADOBE FLASH C.S.3 IN SUBJECT OF ALGEBRA OPERATIONS FOR SMP / MTS - Putri Ratna Sari; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
This research is based on the low interest and low student learning outcomes, the teachers' limited skills in the field of computers, and the limited time that teachers have. The purpose of the research is to develop and understand the feasibility of Interactive multimedia-based Instructional Media with Adobe Flash C.S.3 in the subject of Algebra Operations for SMP / MTs. This research was developed with ADDIE model (1) Analysis: At this stage, the researcher analyzed the curriculum, materials, technology, situation, and condition (2) Design: The researcher provided the reference of the book, arranged the material, made the flowchart and Storyboard. (3) Development: Furthermore, the product development was done, then the product was validated and revised according to the suggestion from 3 persons who expert in the materials,, a person who expert in the media field, and after that was tried forÂ  12 students. (4) Implementation: This product was experienced in a large class with 39 students. (5) Evaluation: Qualitative data from the test was converted into quantitative data on a scale of 5, then the result was converted into qualitative data. This research succeeded in developing the media of mathematics with algebraic material for students of SMP / MTs. The assessment results from a multimedia expert have obtained an average score of 42 with good criteria, as well as the student response rating 54.9216 in good criteria. The Overall Quality of instructional media Obtained an average score of 181.9216 in good criteria. These results indicate that learning media is worthy of use as a medium of learning.